ISOSUBGROUP: an internet tool for generating isotropy subgroups of crystallographic space groups. Issue 5 (29th September 2016) - Stokes, Harold T.; van Orden, Seth; Campbell, Branton J.
Abstract : The new ISOSUBGROUP tool generates the isotropy subgroups of crystallographic space groups arising from arbitrary superpositions of irreducible representations, including magnetic and/or incommensurate cases, without reference to a parent structure. Abstract : ISOSUBGROUP, the newest member of the ISOTROPY Software Suite (http://iso.byu.edu ), generates isotropy subgroups of crystallographic space groups based on superpositions of multiple irreducible representations, along with a wealth of information about each one. Like the original ISOTROPY program, its scope is general rather than being restricted to common types of order parameters of a user‐specified parent structure. But like the newer ISODISTORT program, its user‐friendly interface has menu‐driven selections. This combination of features has been oft requested but unavailable until now. Program output includes information about the subgroup symmetry, ferroic species, phase‐transition continuity, activek vectors, domains and secondary order parameters.